1988
DOI: 10.1016/0014-5793(88)80988-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation enthalpies and pH dependence of phenol hydroxylase from Trichosporon cutaneum, in vitro and in situ

Abstract: The effect ofpH and temperature on phenol hydroxylase in vitro was compared to the corresponding effect on the enzyme in situ, in permeabilized cells. Activation enthalpies in situ were about 75-80% of those in vitro, in both cases decreasing with increasing pH (6.0-8.5). The order of addition of phenol and NADPH affected the Km values for phenol at 25°C, but not at 10°C. The results support the idea that the enzyme in situ is in a more favourable position for catalysis than the purified enzyme and that slow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…PHHY has the capacity to hydroxylate fluoro-, chloro-, amino-, and methyl-substituted phenols [105,106]. Similar to PHBH, the enzyme is not required to bind the phenol substrate for flavin to become reduced by NADPH, however, the affinity for NADPH and the rate constant for reduction increases with target substrate binding [107,108]. …”
Section: The Class a Fpmosmentioning
confidence: 99%
See 1 more Smart Citation
“…PHHY has the capacity to hydroxylate fluoro-, chloro-, amino-, and methyl-substituted phenols [105,106]. Similar to PHBH, the enzyme is not required to bind the phenol substrate for flavin to become reduced by NADPH, however, the affinity for NADPH and the rate constant for reduction increases with target substrate binding [107,108]. …”
Section: The Class a Fpmosmentioning
confidence: 99%
“…The first proposal suggested that substrate bound the enzyme in phenolate form, due to increase in affinity observed at higher pH values [108,109]. However, binding experiments using p -nitrophenol showed the neutral form binding to the oxidized enzyme [110].…”
Section: The Class a Fpmosmentioning
confidence: 99%